Emotion, Conformity, Aggression: Insights from Vocational High School Dynamics: Regulasi Emosi, Konformitas, dan Perilaku Agresif: Dinamika di SMK - Muhammad Anwar Idris Al Mahsuny; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative correlational research investigates the impact of emotion regulation and peer conformity, both individually and concurrently, on aggressive behavior among students at Krembung Islamic Vocational High School. Utilizing a sample of 210 students from a population of 463, the study employed the emotion regulation scale, peer conformity scale, and aggression behavior scale. Multiple regression analysis with SPSS Ver.21 revealed significant results. Emotional regulation demonstrated a negative influence on aggressive behavior, while peer conformity exhibited a positive effect. Moreover, the combined impact of emotional regulation and peer conformity on aggressive behavior was established, with an overall influence of 20.7%. These findings contribute to the understanding of factors influencing aggressive behavior in the context of vocational high school students, emphasizing the importance of emotional regulation and peer dynamics. Highlights : Impact of Emotional Regulation and Peer Conformity: The study explores the individual and combined effects of emotion regulation and peer conformity on aggressive behavior among vocational high school students. Quantitative Correlational Research: Utilizing multiple regression analysis, the research employs a quantitative approach to understand the relationships between emotion regulation, peer conformity, and aggressive behavior. Practical Implications for Education: The findings provide insights for educational institutions in addressing and managing aggressive behavior by considering the roles of emotion regulation and peer conformity among students. Keywords: emotion regulation, peer conformity, aggressive behavior, vocational high school, quantitative correlational.